Istri yang Menolak Tinggal Bersama Suami karena Tuntutan Pekerjaan PPPK Perspektif KHI - Salsabila Hasyim; Ibnu Radwan Siddik Turnip (CV Global Research Publication, 2026)
One of the issues faced by families of Government Employees with Work Agreements (PPPK) after receiving their official appointment letters is job placement far from their place of residence, forcing married couples to live apart temporarily. This study aims to analyze the phenomenon of wives refusing to live with their husbands due to employment, based on a review of the Compilation of Islamic Law (KHI). This study is an empirical legal study employing a legal and sociological-legal approach. Primary data were obtained through interviews with married couples and community leaders, while secondary data were sourced from Law No. 1 of 1974 on Marriage, the Compilation of Islamic Law, and other legal materials. Data analysis was conducted qualitatively. The results show that some wives choose to remain at home due to their husbands’ distant work locations and high transportation costs, making living together currently unfeasible. At first glance, this situation appears to contradict the KHI, particularly Article 83(1) regarding a wife’s duty to be dutiful to her husband and Article 84(1) concerning nusyuz. However, the assessment of nusyuz cannot be based solely on the wording of the article. As long as the wife maintains communication, fulfills her household responsibilities, and does not neglect her rights and obligations toward her husband, such a situation can be viewed as a valid reason and should not automatically be categorized as nusyuz. From the perspective of family resilience, temporary separation does not always have a negative impact if the husband and wife maintain a harmonious relationship, understand one another, and are able to adapt to social and economic demands.